(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Climate change in the 21st century threatens global food security through reduced agricultural productivity, disrupted food supply chains, increased food-borne illness, land degradation, and rising food prices. Extreme weather events like droughts and floods, altered temperature and rainfall patterns, and rising CO2 levels directly impact crop yields and the nutritional quality of food. Vulnerable populations suffer disproportionately as they have less capacity to adapt to climate shocks and other stressors, highlighting the need for climate-smart and nutrition-sensitive food systems and integrated policies to achieve both climate action and "zero hunger". This review envisages pointing out the factors which all stakeholders and policymakers must consider and act judiciously to combat climate change issues collectively to ensure global food security.